Pedagogical Challenges and Impacts of the Merdeka Curriculum for Students with Special Needs - Novembli, Meta Silfia; Wahyuni, Sri; Hasanah, Nisaul; Fitriani, Dina; Hartati, Peby Tri (Universitas Lancang Kuning, 2025)
This study explores the challenges and impacts of the Merdeka Curriculum implementation in Special Needs Schools (SLB) in Pekanbaru on students with special needs. Using a quantitative survey method with a total sampling approach involving SLB teachers in Pekanbaru (n45), data was collected through questionnaires, interviews, and documentation. The analysis utilized Descriptive Statistics and Qualitative data analysis was conducted on interview transcripts and documents. The research results indicate significant challenges in teacher readiness (65% need more training, 25% low), availability of resources and infrastructure (70% minimal), and curriculum and assessment adaptation (60% difficulty in adaptation, 55% difficulty in assessment), with most falling into the